Amyloid-β Load Is Related to Worries, but Not to Severity of Cognitive Complaints in Individuals With Subjective Cognitive Decline: The SCIENCe Project - Verfaillie, Sander C. J.; Timmers, Tessa; Slot, Rosalinde E. R.; van der Weijden, Chris W. J.; Wesselman, Linda M. P.; Prins, Niels D.; Sikkes, Sietske A. M.; Yaqub, Maqsood; Dols, Annemiek; Lammertsma, Adriaan A.; Scheltens, Philip; Ossenkoppele, Rik; et al. (Frontiers in Aging Neuroscience, 2019)
Objective: Subjective cognitive decline (SCD) is associated with an increased risk of Alzheimer’s Disease (AD). Early disease processes, such as amyloid-β aggregation measured with quantitative PET, may help to explain the phenotype of SCD. The aim of this study was to investigate whether quantitative amyloid-β load is associated with both self- and informant-reported cognitive complaints and memory deficit awareness in individuals with SCD. Method: We included 106 SCD patients (mean±SD age: 64±8, 45%F) with 90 minutes dynamic [18F]florbetapir PET scans. We used the following questionnaires to assess SCD severity: cognitive change index (CCI, self & informant reports; 2x20 items), subjective cognitive functioning (SCF, 4 items), and five questions “Do you have complaints?” (yes/no) for memory, attention, organization and language), and “Does this worry you? (yes/no)”. The Rivermead Behavioral Memory Test (RBMT)-Stories (immediate and delayed recall) was used to assess objective episodic memory. To investigate the level of self-awareness, we calculated a memory deficit awareness index (Z-transformed (inverted self-reported CCI minus episodic memory); higher index, heightened self-awareness) and a self-proxy index (Z-transformed self- minus informant-reported CCI). Mean cortical [18F]florbetapir binding potential (BPND) was derived from the PET data. Logistic and linear regression analyses, adjusted for age, sex, education, and depressive symptoms, were used to investigate associations between BPND and measures of SCD. Results: Higher mean cortical [18F]florbetapir BPND was associated with SCD-related worries (odds ratio=1.76 [95%CI=1.07±2.90]), but not with other SCD questionnaires (informant and self-report CCI or SCF, total scores or individual items, all p>0.05). In addition, higher mean cortical [18F]florbetapir BPND was associated with a higher memory deficit awareness index (Beta=0.55), with an interaction between BPND and education (p=0.002). There were no associations between [18F]florbetapir BPND and self-proxy index (Beta=0.11). Conclusions: Amyloid-β deposition was associated with SCD-related worries and heightened memory deficit awareness (i.e. hypernosognosia), but not with severity of cognitive complaints. Our findings indicate that worries about self-perceived decline may reflect an early symptom of amyloid-β related pathology rather than subjective cognitive functioning.